Tasawuf Abdullah bin Alwi Al Haddad - 494674 M. A. Achlami H. S. (Jakarta : Universitas Islam Negeri Syarif Hidayatullah, 2006)
Thesis (Ph.D (Ilmu Agama Islam)) - Universitas Islam Negeri Syarif Hidayatullah, 2006